Caracterização estrutural e funcional de hemoglobinas de três espécies de aves - Silva, Hugo Ribeiro da (Universidade Federal de São Carlos, 2003)
Hemoglobin electrophoretic patterns, oxygen equilibrium experiments using unfractionated blood, stripped hemoglobin at 4oC, 21oC, 40oC, as well as the effect of inositol hexaphosphate (IHP) and 2,3-biphosphoglycerate (BPG), and the qualitative and quantitative determination of intraerythrocytic organic phosphate were done, in three species of Aves: Athene cunicularia – owl (Order Strigiformes, Family Strigidae), Coragyps atratus - vulture (Order Ciconiformes, Family Cathartidae) and Mimus saturninus - mocking bird (Order Passariformes Family Mimidae). On starch gel electrophoresis, pH 8.6, A. cunicularia and C. atratus showed one slow anodic major component and one fast minor components, a typical bird hemoglobin pattern. On the same electrophoretic conditions, M. saturninus showed two anodic major components, instead one major and one minor. Stripped hemoglobins at the three temperatures, in the presence of IHP, BPG, and blood showed normal Bohr effect and n values (Hill plots) were close to one, indicating very low or no cooperativity. Oxygen affinities were temperature-dependent (as lower the temperature higher is the affinity), BPG modulation was low, IHP was very effective as negative modulator. Vulture hemoglobin showed the highest P50 value, while the owl and the mocking bird presented lower and similar oxygen affinity to each other. No AMP, GTP and BPG were found, only ADP, ATP and inositols were detected in the erythrocytes of the three species. Inositol pentaphosphate (IP5) was the most abundant intraerythrocytic organic phosphate in the 3 species. A. cunicularia showed also inositol tetraphosphate and C. atratus and M. saturninus showed IHP, besides IP5. Although the three species belong to different Orders, have different habit; the functional properties of their hemoglobins are very similar. One hypothesis to explain such similarity is that the avian system to deliver and discharge oxygen to the tissues are so efficient, that works properly in a wide range of situations
Keywords: Aves; Hemoglobina; Efeito Bohr; Eletroforese; Inositol pentafosfato; Equilíbrio de oxigenação; CIENCIAS BIOLOGICAS::GENETICA